Potensi Wisata Halal dalam Meningkatkan Kesejahteraan Masyarakat - Gustina Gustina; Yenida Yenida; Novadilastri Novadilastri (Politeknik Negeri Padang, 2019)
Tourism is a sector that is growing very rapidly at this time in Indonesia. The purpose of this study is to explore the potential of halal tourism owned by Air Manis Beach (PAM) which can increase income and welfare of the surrounding community. This research is a qualitative study which uses primary data as the source of the data. Data obtained through field observations and in-depth interviews with selected respondents. These respondents consisted of 10 business people or community who are in PAM. The results of this study indicate that the community around PAM including business actors in PAM feel the great potential of PAM tourism in increasing employment opportunities, business chances and increasing their welfare. The hoping is that the government can cooperate better with the community and business practitioners in PAM in terms of management, development and improvement of these tourist destinations.